2020
DOI: 10.1021/acs.analchem.9b04999
|View full text |Cite
|
Sign up to set email alerts
|

Toward CO2 Electroreduction under Controlled Mass Flow Conditions: A Combined Inverted RDE and Gas Chromatography Approach

Abstract: The use of rotating disk electrodes (RDEs) is probably the most convenient way of studying simple electrode reactions under well-defined transport conditions. Standard RDEs become, however, less expedient when the studied electrode process is a complex one, leading to the formation of various reaction products. In these cases, the accurate detection and quantification of the formed products are desirable. If the formed products are gaseous, then the usual way of quantifying them is the use of online gas chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…The cylinder electrode area in the RCE gastight cell is 15 times larger than those common to rotating disk electrodes (RDEs) (disk areas are typically around 0.2 cm 2 ) and because of its geometry, the RCE does not suffer from surface blockage from bubbles evolved in the process which has been a limiting factor for RDE systems. 5 The large geometric area to electrolyte volume in the gas-tight RCE cell results in detection limits for liquid products in the order of few μM in hour-long experiments and the on-line detection of gas products in the order of 1 ppm which are equivalent to partial current densities of less than 10 μA cm À2 . The gastight RCE system presented here offers access to the rigorous study of electrode kinetics even at low current densities in low roughness, idealized electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cylinder electrode area in the RCE gastight cell is 15 times larger than those common to rotating disk electrodes (RDEs) (disk areas are typically around 0.2 cm 2 ) and because of its geometry, the RCE does not suffer from surface blockage from bubbles evolved in the process which has been a limiting factor for RDE systems. 5 The large geometric area to electrolyte volume in the gas-tight RCE cell results in detection limits for liquid products in the order of few μM in hour-long experiments and the on-line detection of gas products in the order of 1 ppm which are equivalent to partial current densities of less than 10 μA cm À2 . The gastight RCE system presented here offers access to the rigorous study of electrode kinetics even at low current densities in low roughness, idealized electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to gain insights into fundamental electrocatalytic reaction kinetics and to create a basis for the rational design of electrochemical reactors, we have developed a gastight rotating cylinder electrode (RCE) cell that allows the detection and quantification of gas and liquid products generated on RCEs under the conditions of well‐defined hydrodynamics (Figure 1). The cylinder electrode area in the RCE gastight cell is 15 times larger than those common to rotating disk electrodes (RDEs) (disk areas are typically around 0.2 cm 2 ) and because of its geometry, the RCE does not suffer from surface blockage from bubbles evolved in the process which has been a limiting factor for RDE systems 5 . The large geometric area to electrolyte volume in the gas‐tight RCE cell results in detection limits for liquid products in the order of few μM in hour‐long experiments and the on‐line detection of gas products in the order of 1 ppm which are equivalent to partial current densities of less than 10 μA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high activity of proton reduction at low overpotentials, the current efficiencies found for CO in acidic media are usually low, especially on electrodes with low roughness. In fact, only in a few works in the literature, CO 2 R has been investigated (at small scale) in acidic media 10,11,20,21 . Recent work from Bondue et al 10 has indicated that proton reduction can be fully suppressed in acidic media, as long as the rate of CO/OH − formation from CO 2 R is high enough to compensate the mass transfer of protons to the electrode surface.…”
mentioning
confidence: 99%
“…Clearly, more work is needed to understand the various effects of mass transport on ECR. Here, a recently developed inverse rotating disk electrode 21 that enables the use of gas chromatography may enable more detailed studies on the effect of mass transport. But regardless of these controversial results with regard of the effect of mass transport on ECR, it is generally accepted that the transport of the reactant CO 2 limits the ECR current density that can be achieved in liquid electrolytes.…”
Section: Introductionmentioning
confidence: 99%